Genomics reveal local skin immune response key to control sarcoptic mange in Iberian ibex (Capra pyrenaica) - Arián Ráez-Bravo; José Enrique Granados; José Espinosa; Lara Nonell; Emmanuel Serrano; Eulàlia Puigdecanet; Marta Bódalo; Jesús M. Pérez; Ramón C. Soriguer; Francisco Javier Cano-Manuel; Paulino Fandos; Jorge Ramón López-Olvera (BMC Genomics)
Abstract Background Sarcoptic mange is an emerging and neglected contagious skin disease caused by the mite Sarcoptes scabiei, affecting humans, domestic animals, and wildlife. Mange is the main disease and a major concern for the management and conservation of populations of Iberian ibex (Capra pyrenaica), a medium-sized mountain ungulate endemic to the Iberian Peninsula and Northern Pyrenees. Differences in host-parasite interaction and host immune response determine mange clinical outcome, but little is known about the related differences in gene expression. This study determined blood and skin gene expressions in S. scabiei-experimentally infested Iberian ibexes. Results Infestation with S. scabiei promoted immune and inflammatory genomic responses both in skin and blood, with two different clinical outcomes: either severe infestation or recovery. Sarcoptes scabiei induced local skin immunosuppression to favour its multiplication and establishment of the infestation in the host. Skin gene expression was mostly inflammatory and inefficient to control mange in the severely infected ibexes. Conversely, the immune skin response of the recovered ibexes effectively recognised S. scabiei and activated T-cells, limiting the infestation. Consequently, inflammation-related genes were more expressed in the blood of the severely infested ibexes than in those that recovered. Conclusions The results demonstrate that skin local cellular immune response is key to control sarcoptic mange and prevent the systemic spread of the disease and the associated inflammatory response. These results will be useful to understand the pathogenesis and drivers of the differential outcome of mange at individual scale, and the population and ecological consequences of such variability in Iberian ibex, as well as in other wildlife species, domestic animals, and humans.